PENGARUH SIFAT MACHIAVELLIAN, LOCUS OF CONTROL, DAN EQUITY SENSITIVITY TERHADAP PENGHINDARAN PAJAK DENGAN KEPUTUSAN ETIS SEBAGAI VARIABEL INTERVENING - Ramadhani, Tri Suci; -, Kennedy; -, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of machiavellian behaviour, locus of control, and equity sensitivity on tax avoidance with ethical decision as an intervening variable. The population in this study were taxpayer who doing business and employment free that is registered in the Tax Office Pratama Pekanbaru Senapelan. The sampling method used in this study is convenience sampling method. The sample used in this study were 100 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS 17.0. The result of this study indicated that (1) machiavellian behaviour has a significant influence on the ethical decision, (2) locus of control has significant effect on the ethical decision, (3) equity sensitivity has not a significant influence on the ethical decision,(4) ethical decision has significant effect on tax avoidance.Keywords: machiavellian, locus of control, equity sensitivity, tax avoidance, and ethical decision.